Selection of Suitable Provenances of Acacia nilotica for Sodic Soil - Sharma, S. D.; Khan, G. H.; Prasad, K. G. (Indian Forester, 2000)
A provenance trial of Acacia nilotica was conducted in sodic soils of Sultanpur District in Uttar Pradesh. Out of the ten provenances under test, the Sholapur (Maharashtra) was found to be most suitable provenance followed by Dhaund (Maharashtra) for the sodic site. Haldwani (Uttar Pradesh) provenance proved to be most interior for this site.